Self-Efficacy as a Dominant Predictor of Learning Motivation: An Analysis of the Role of Assertiveness and Social Support in Madrasah Aliyah Students - Burhanuddin Kaloko; Saiful Akhyar Lubis; Nurussakinah Daulay (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Learning motivation is a key psychological factor influencing students’ academic persistence and achievement, particularly within faith-based educational settings such as Madrasah Aliyah. This study examines the influence of assertiveness and self-efficacy on students’ learning motivation, with social support as a mediating variable. A quantitative path analysis was conducted using a sample of 275 students selected via proportional random sampling from three madrasahs in Dairi Regency, Indonesia. Data were collected using validated Likert-scale questionnaires and analyzed with Structural Equation Modeling using Partial Least Squares (SEM-PLS 4.1). The results show that assertiveness and self-efficacy significantly affect social support (β = 0.228; β = 0.260) and learning motivation (β = 0.180; β = 0.293). Social support also positively affects learning motivation (β = 0.259). Mediation analysis reveals that social support weakly mediates the effect of assertiveness on learning motivation yet significantly mediates the effect of self-efficacy on learning motivation. These findings highlight the importance of psychological empowerment in fostering student motivation. Keywords: learning motivation, self-efficacy, assertiveness, social support, academic resilience, quality education, student well-being